Grooming of fouling-release coatings to control marine fouling and determining how grooming affects the surface. Issue 4 (21st April 2022) - Dahlgren, Joseph; Foy, Lauren; Hunsucker, Kelli; Gardner, Harrison; Swain, Geoff; Stafslien, Shane J.; Vanderwal, Lyndsi; Bahr, James; Webster, Dean C.
Abstract: Grooming may be an effective technique to control marine biofouling without damaging the coating or discharging active ingredients into the environment. This study assessed the grooming performance of three experimental biocide-free siloxane polyurethane (SiPU) fouling-release coatings. Coatings were statically immersed in Port Canaveral, Florida, and groomed every two weeks for five months using three different brush types. The ungroomed panels became heavily fouled with biofilm, tubeworms, barnacles, and bryozoans. Two of the brushes were able to control the fouling with a coverage of <5%. The commercial silicone elastomer coating was damaged from grooming procedures, while the SiPU coatings were not. Laboratory biological assays were carried out and mirrored the grooming results. Through surface characterization techniques, it was concluded that the coatings were unaffected by the grooming procedures. This study shows that marine fouling on durable SiPU fouling-release coatings can be controlled via grooming without damage or changing the surface properties.